The future of pharmaceutical care in Malaysia: pharmacy students’ perspectives - Elnaem, Mohamed Hassan Abdelaziz; Jamshed, Shazia Qasim; Elkalmi, Ramadan Mohamed Mahmod (International Pharmaceutical Federation, 2017)
Objective: To investigate the attitudes of pharmacy students toward pharmaceutical care (PC), perceptions of their preparedness level and barriers to the provision of PC in Malaysia.